KONTRIBUSI LAYANAN BIMBINGAN INFORMATIF STUDI KARIR DALAM MENINGKATKAN MOTIVASI BELAJAR PADA SISWA KELAS XII - Abdul Muhid; Muhammad Muhlasin; Arienda Fintania (Prodi Bimbingan Konseling Universitas Negeri Manado, 2022)
The enthusiasm of students in achieving learning goals is influenced by intrinsic and extrinsic factors. Intrinsic factors include motivation, talent, interest, and personality. While extrinsic factors include the role of parents, the learning process at school, and the social environment. Especially in class XII students who are in a tentative period in determining their careers. Career planning and maturity are obtained through informative guidance services. Therefore, this study aims to determine the contribution of informative career study guidance services in increasing learning motivation. The research method focuses on a literature review approach or literature review. The results showed that there was a contribution of informative guidance services in increasing learning motivation in class XII students.